Ab Initio Study of Energy Transfer Pathways in Dinuclear Lanthanide Complex of Europium(III) and Terbium(III) Ions - Romanova, Ksenia A; Freidzon, Alexandra Ya; Bagaturyants, Alexander A; Galyametdinov, Yury G (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2014)
An ab initio XMCQDPT2/CASSCF study of energy transfer processes in the dinuclear lanthanide complex [(Acac)3Eu(μ-Bpym)Tb(Acac)3] (Acac is acetylacetonate, and Bpym is 2,2′-bipyrimidine) and a corresponding computational procedure are presented. Because ligands in lanthanide complexes weakly interact with each other, the large dinuclear complex bearing seven organic ligands is divided into fragments that reproduce the electrostatic effects of the ions on the electronic and geometrical structure of the ligands. The multireference XMCQDPT2/CASSCF approach is directly applied to these relatively small fragments with reasonable computational cost. The calculated energies of the singlet and triplet excited states agree well with the experiment. Based on the calculated energies, the energy level diagrams of the complex are constructed and intramolecular energy transfer channels are determined.